2016
DOI: 10.1177/1077801216634467
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Sexual Assault Perpetration Among Heterosexually Active Young Men

Abstract: Data from an online community sample of young men were analyzed to test predictors of sexual assault perpetration. We used structural equation modeling to test the relative contributions of specific sub-types of childhood adversity to subsequent sexual aggression. Mediators included hostile masculinity, impersonal sexual behavior and attitudes, and substance use variables. Findings suggested that childhood sexual abuse had direct and mediated effects on sexual assault perpetration, but hostile masculinity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 40 publications
4
45
0
2
Order By: Relevance
“…Recent research has also shown that variables representing manipulation tactics and substance use or force load onto separate factors, indicating that it may be useful to separate VSC from incapacitation and force as tactics to obtain sex from unwilling partners [ 38 ]. We attest, as with many other scholars, that verbal sexual coercion is just one tactic of sexual assault on a continuum ranging from non-forceful verbal tactics to incapacitation to physical force [ 26 , 34 , 36 , 37 , 39 , 40 , 43 , 44 , 46 , 66 , 71 , 75 , 76 , 77 , 78 , 79 , 80 ]. There are many reasons articulated throughout this paper as to why we believe that this conceptualization is necessary, but it is also worth noting that research has suggested that women experience similar levels of distress despite the type of perpetration tactic [ 97 ], suggesting the utility of including tactics of verbal sexual coercion on a continuum with other perpetrator tactics.…”
Section: Sexual Coercionsupporting
confidence: 59%
See 2 more Smart Citations
“…Recent research has also shown that variables representing manipulation tactics and substance use or force load onto separate factors, indicating that it may be useful to separate VSC from incapacitation and force as tactics to obtain sex from unwilling partners [ 38 ]. We attest, as with many other scholars, that verbal sexual coercion is just one tactic of sexual assault on a continuum ranging from non-forceful verbal tactics to incapacitation to physical force [ 26 , 34 , 36 , 37 , 39 , 40 , 43 , 44 , 46 , 66 , 71 , 75 , 76 , 77 , 78 , 79 , 80 ]. There are many reasons articulated throughout this paper as to why we believe that this conceptualization is necessary, but it is also worth noting that research has suggested that women experience similar levels of distress despite the type of perpetration tactic [ 97 ], suggesting the utility of including tactics of verbal sexual coercion on a continuum with other perpetrator tactics.…”
Section: Sexual Coercionsupporting
confidence: 59%
“…Many scholars use the terms sexual coercion and sexual assault interchangeably or that sexual coercion encompasses all types of perpetration tactics that lead to sexual assault [ 59 , 74 ]. In these studies, sexual coercion is defined as a continuum of tactics to elicit sexual activity from unwilling partners ranging from non-forceful verbal tactics to physical force, with taking advantage of women due to voluntary or administered alcohol and/or drug intoxication somewhere in the middle [ 26 , 34 , 36 , 37 , 39 , 40 , 43 , 44 , 46 , 66 , 71 , 75 , 76 , 77 , 78 , 79 , 80 ]. Sexual coercion has also been specifically defined as tactics used following a partner’s refusal to sexual advances [ 36 , 46 , 48 , 70 , 81 ].…”
Section: Sexual Coercionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diminished economic opportunities in neighborhoods and high unemployment are also associated with perpetration of child abuse and neglect, 34 intimate partner violence, 24 self-directed violence, 35,36 sexual violence, 37,38 and youth violence. 39 Also, norms in societies or communities that support strict gender roles for men and women are associated with perpetration of child abuse and neglect, 40,41 intimate partner violence, 4245 sexual violence, 16,18,38,42,46,47 teen dating violence, 48,49 youth violence, 50 suicide, 51 and bullying, 52,53 and norms supporting aggression or coercion are associated with almost all forms of violence. 24,40,49,52,5456 …”
Section: Risk and Protective Factors Across The Social Ecology*mentioning
confidence: 99%
“…De otro lado, se ha identificado que experiencias tempranas de socialización parental orientadas al maltrato físico y psicológico, abuso y negligencia (Casey et al, 2017) son fuertes predictores de la agresividad, la falta de empatía y la conducta antisocial en la infancia y la adolescencia. El estudio de Campaert et al (2018) evidencia que "en la infancia tardía, el castigo corporal repetido se asoció con niveles más altos de desvinculación moral un año después, y esta relación fue mediada por un aumento en la aprobación de agresión por parte de los padres" (p. 2656).…”
Section: Mécanismes De Déconnexion Morale Et Sa Relation Avec L'empatunclassified